Chapter Tussen marge en middelpunt - voormoeders van genderstudies in Utrecht - Waaldĳk, Berteke (Amsterdam University Press, 2023)
In this essay, Berteke Waaldĳk outlines the early development of gender studies in Utrecht through the course 'Between Margin and Centre, Women in Culture and Society'. The course lent itself perfectly to an interdisciplinary approach and addressed many interrelated themes, such as gender, colonialism, racism and a politics of location. The course was also an example of close collaboration between Berteke Waaldĳk and Rosemarie Buikema, whose ideas and academic careers influenced each other.